A 57 kB Genomic Deletion Causing CTNS Loss of Function Contributes to the CTNS Mutational Spectrum in the Middle East - Najafi, Maryam; Tamandani, Dor Mohammad Kordi; Azarfar, Anoush; Bakey, Zeineb; Behjati, Farkhondeh; Antony, Dinu; Schüle, Isabel; Sadeghi-Bojd, Simin; Karimiani, Ehsan Ghayoor; Schmidts, Miriam (Frontiers in Pediatrics, 2019)
Background: Nephrotic Cystinosis, the most common cause of renal Fanconi syndrome, is a lysosomal transport disorder with an autosomal recessive inheritance pattern. A large number of mutations in CTNS have been identified as causative to date. A 57kb deletion encompassing parts of CTNS is most commonly identified in Caucasians but this allele has not been identified in individuals of Eastern Mediterranean, Middle Eastern, Persian or Arab origin to date. Methods and Results: Implementing whole exome sequencing (WES) in a consanguineous Iranian family, we identified this large deletion affecting CTNS in a patient initially presenting with hypokalemic metabolic alkalosis symptoms and considerable proteinuria. Conclusion: We show WES is a cost and time efficient genetic diagnostics modality to identify the underlying molecular pathology in Cystinosis individuals and provide a summary of all previously reported CTNS alleles in the Middle east population. Our work also highlights the importance to consider the 57-kb deletion as underlying genetic cause in non-European populations, including the Middle East. Limited diagnostic modalities for Cystinosis in developing countries could account for the lack of previously reported cases in these populations carrying this allele. Further, our findings emphasize the utility of WES to define genetic causes in clinically poorly defined phenotypes and demonstrate the requirement of Copy number variation (CNV) analysis of WES data.